Acoustic Properties Of Micro-Perforated Panels Made From Oil Palm Empty Fruit Bunch Fiber Reinforced Polylactic Acid - Sekar, Vignesh; Kassim, Dg Hafizah; Putra, Azma; Noum, Se Yong Eh; Sivanesan, Sivakumar; Chin, Kok Chun; Wong, Yi San (Tech Science Press, 2021)
This paper presents the development and performance of Micro-Perforated Panels (MPP) from natural fiber reinforced composites. The MPP is made of Polylactic Acid (PLA) reinforced with Oil Palm Empty Fruit Bunch Fiber (OPEFBF). The investigation was made by varying the fiber density, air gap, and perforation ratio to observe the effect on the Sound Absorption Coefficient (SAC) through the experiment in an impedance tube. It is found that the peak level of SAC is not affected, but the peak frequency shifts to lower frequency when the fiber density is increased. This phenomenon might be due to the presence of porosity in the inner wall of the holes. Increasing or decreasing the air gap and perforation ratio shifts the peaks of acoustic absorption either way